Study of magnetoelectrodeposition of lanthanum (III) chloride heptahydrate leached with sulfuric acid. Issue 1 (1st April 2022) - Cahyanegoro, A. G.; Sudibyo,; Badaruddin, M.; Sugiyanto,; Nurjaman, Fajar; Supriyatna, Yayat Iman; Prasetyo, Erik
Abstract: A rare-earth element (REE) is one of the minerals with many resources in Indonesia and lanthanum is one of REE. Lanthanum is widely used as a material for x-ray screens, glass lenses, optical fiber, capacitor batteries, and ceramics. Electrodeposition is a metal deposition process. The advantages of electrodeposition are easy and inexpensive. The method is simple since it can be done at room temperature, and it is inexpensive because it only requires basic equipment. However, there is a drawback to conventional electrodeposition: the roughness of the resultant layer (non-uniform crystal growth). Magnetoelectrodeposition (MED) is a solution for solving this problem. We employed the MED method in this study, which is the electrodeposition procedure under the influence of a magnetic field, and there has been no previous research on lanthanum MED. The electrode area, magnetic field strength, electroactive concentration, diffusion coefficient, and kinematic electrolyte viscosity were variables used in this study. The lanthanum MED in this study used 98% lanthanum (III) chloride heptahydrate (LaCl3 .7H2 O) for analysis from Merck, which was leached at a particular concentration of sulfuric acid (H2 SO4 ), using platinum electrodes in three electrochemical cells, and varying the magnetic field strength from 0 to 0.08 Tesla. The results showed that the stronger the magnetic field, the greater the limiting current for lanthanum electrodeposition. The effect of electrode area and electroactive concentration also gives rise to the limiting current. Meanwhile, the viscosity of the solution and the diffusion coefficient will cause a reduction in limiting the current value.